Perancangan Pop-Up Book sebagai Media Pengenalan Pengendalian Diri untuk Anak Usia 5-6 Tahun - Hariyanto, Agnes Tea Kirana; Nirwana, Aditya; Sukmaraga, Ayyub Anshari (Citradirga : Jurnal Desain Komunikasi Visual dan Intermedia, 2023)
Indonesia, known for its friendly nature, is experiencing symptoms of moral degradation, even among elementary school children. This is also due to various factors such as exposure to harmful content and lack of early character education. The concept of self-control, as the foundation for other character education, should be taught to children so they can differentiate what should and shouldn't be done. The purpose of this design is to introduce self-control to children through an informal learning medium: a pop-up storybook titled "Even Heroes Need Self-Control". To achieve this goal, the designer collected qualitative data through observation, interviews, and literature studies, which served as a reference for the design process using the Research and Development method. The final product is a 14-page hardcover book, with merchandise such as secondary packaging, interactive magnetic poster, bucket hat, sanitizer, water bottle, and enamel pin. The success indicator for this design is an introduction of self-control, demonstrated by the ability to mention examples of self-control that can be practiced in daily life.